Hubungan Lama Membaca Buku KIA (Kesehatan Ibu dan Anak) dengan Pengetahuan dan Sikap Ibu Hamil Terhadap Kehamilan: Correlation Reading Duration of MCH (Mother and Child Health) Handbook with Knowledge and Attitudes of Pregnant Women Towards Pregnancies - Amalia, Riza; Rahardjo Putri, Noviyati; Tunggal Mutika, Winie; Laela Megasari, Anis (Indonesian Journal of Midwifery (IJM), 2023)
The maternal mortality rate in Indonesia is still far from the MDGs target. The government's policy to overcome this problem is by providing MCH books since pregnancy. Unfortunately, there are still many pregnant women who do not read the MCH handbook and still consider the MCH handbook only as documentation of pregnancy records. The purpose of this study was to see the relationship between the duration of reading time and the knowledge and attitudes of pregnant women during pregnancy. The research method used a survey method with a cross sectional approach. This research was conducted from June to July 2022 with a total sample of 268 pregnant women on Java Island who were taken using a random method. The research instrument used a questionnaire in the form of a Google form. Data analysis used univariate analysis in the form of frequency distribution and bivariate analysis used the chi-square test with a 95% confidence level. The statistical test results obtained a p value of 0.037 or less than 0.05 and an OR value of 1.6. These results indicate that there is a relationship between the duration of reading the MCH handbook and the respondent's knowledge of the MCH handbook. The results of another statistical test obtained a p value of 0.003 and an OR value of 2.4. This result shows that there is a relationship between knowledge of the MCH handbook and the attitude of the respondents. Based on this, pregnant women must have a duration of time to read MCH in order to have sufficient knowledge and a healthy attitude according to the information contained in the MCH handbook.   Abstrak Angka kematian ibu di Indonesia masih jauh dari target MDGs. Kebijakan pemerintah untuk mengatasi permasalahan tersebut dengan pemberian buku KIA sejak hamil.  Sayangnya masih banyak ibu hamil yang tidak membaca buku KIA dan masih menganggap buku KIA hanya sebagai dokumentasi catatan kehamilan saja. Tujuan penelitian ini untuk melihat hubungan durasi waktu membaca dengan pengetahuan dan sikap ibu hamil selama kehamilan. Metode penelitian menggunakan metode survey dengan pendekatan cross sectional. Penelitian ini dilakukan pada bulan Juni – Juli 2022 dengan populasi semua ibu hamil di Pulau Jawa, total sampel 268 ibu hamil yang diambil menggunakan metode acak. Instrumen penelitian menggunakan kuesioner dalam bentuk google form. Analisis data menggunakan analisis univariat berupa distribusi frekuensi dan analisis bivariat menggunakan uji chisquare dengan tingkat kepercayaan 95%. Hasil uji statistik didapatkan p value 0,037 dan nilai OR 1,6. Hasil tersebut menunjukkan ada hubungan antara durasi baca buku KIA dengan pengetahuan responden tentang buku KIA.hasil uji statistik lain didapatkan p value 0,003 dan nilai OR 2,4. Hasil ini menunjukkan ada hubungan antara pengetahuan tentang buku KIA dengan sikap responden. Berdasarkan hal tersebut maka ibu hamil harus memiliki durasi waktu membaca KIA setidaknya 29 menit/ pekan agar memiliki pengetahuan cukup dan sikap sehat sesuai dengan informasi yang ada dalam buku KIA.